Constitutive descriptions for hot compressed 2124-T851 aluminum alloy over a wide range of temperature and strain rate - Lin, Y.C.; Xia, Yu-Chi; Chen, Xiao-Min; Chen, Ming-Song (Computational materials science, 2010)
The compressive deformation behaviors of 2124-T851 aluminum alloy were investigated over a wide range of temperature and strain rate on Gleeble-1500 thermo-simulation machine. The results show that the true stress–true strain curves exhibit a peak stress at a very small strain, after which the flow stresses decrease until high strains, showing a dynamic flow softening. The measured flow stress was modified by friction correction, and the corrected flow stresses are lower than the measured ones, which nicely reflect negative effects of the interfacial friction on the flow stress. A revised model is proposed to describe the relationships of the flow stress, strain rate and temperature of 2124-T851 aluminum alloy at elevated temperatures. The stress–strain values of 2124-T851 aluminum alloy predicted by the proposed model well agree with experimental results, which confirmed that the revised deformation constitutive equation gives an accurate and precise estimate for the flow stress of 2124-T851 aluminum alloy.